Diversidade genética entre populações de Plagioscion squamosissimus (Heckel, 1840) (Perciformes, Sciaenidae) de cinco bacias hidrográficas neotropicais - Diamante, Nathalia Alves (2015)
The Sciaenidae has the largest number of species within the order Perciformes and it is a major world fishery resource, with about 70 genera and 270 species established in the Atlantic, Indian and Pacific. Phylogenetic relationships and taxonomy of some genera and species of this family are still controversial. Therefore, morphological and molecular studies have been conducted to identify and correctly classify of species Sciaenidae and also to estimate their phylogenetic position. Twenty species of Scianidae are recognized in South America, among them five are the Plagioscion genus. The croaker, Plagioscion squamosissimus, is native to the Amazon basin, Tocantins and Parnaíba and it was introduced in Northeast reservoirs in Brazil and in the Paraná River basin. Knowing this, the first chapter of this work is a scientometric analysis of the publications that used mitochondrial or nuclear DNA molecular markers in studies of the family Sciaenidae. The second chapter includes a study to assess the genetic diversity among native and introduced populations of P. squamosissimus Brazilian basins, through the analysis of sequences of the mitochondrial gene ATPase 6/8. The elucidation of the genetic relationships between isolated populations of the Parnaíba river basin, the Tocantins river basin, the Amazon river basin and introduced populations in the upper Paraná river basin and the basin of the river São Francisco contribute to the knowledge of P. squamosissimus biology.